1999
DOI: 10.1021/bc980125h
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficiency Intracellular Magnetic Labeling with Novel Superparamagnetic-Tat Peptide Conjugates

Abstract: A biocompatible, dextran coated superparamagnetic iron oxide particle was derivatized with a peptide sequence from the HIV-tat protein to improve intracellular magnetic labeling of different target cells. The conjugate had a mean particle size of 41 nm and contained an average of 6.7 tat peptides. Derivatized particles were internalized into lymphocytes over 100-fold more efficiently than nonmodified particles, resulting in up to 12.7 x 10(6) particles/cell. Internalized particles localized in cytoplasm and nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
705
1
5

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 870 publications
(721 citation statements)
references
References 26 publications
10
705
1
5
Order By: Relevance
“…Thus, the imaging capability provided is not from the SPIO intrinsically, but through their influence on longitudinal and transverse relaxation of the surrounding nuclei. Although the ability of SPIO to significantly reduce the spin-spin relaxation (T2) time is generally relied on for generating MR contrast, 68,99 it has also been demonstrated that SPIO can generate sufficient T1 contrast for biomedical applications as well; SPIO possess both high R1 and R2 relaxivities. 118,127 Upon removal of the magnetic field, Brownian motion is sufficient to randomize the SPIO orientations leaving no magnetic remanence.…”
Section: Magnetismmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the imaging capability provided is not from the SPIO intrinsically, but through their influence on longitudinal and transverse relaxation of the surrounding nuclei. Although the ability of SPIO to significantly reduce the spin-spin relaxation (T2) time is generally relied on for generating MR contrast, 68,99 it has also been demonstrated that SPIO can generate sufficient T1 contrast for biomedical applications as well; SPIO possess both high R1 and R2 relaxivities. 118,127 Upon removal of the magnetic field, Brownian motion is sufficient to randomize the SPIO orientations leaving no magnetic remanence.…”
Section: Magnetismmentioning
confidence: 99%
“…6 Of particular interest is the conjugation of membrane translocating signals such as HIV-Tat and polyArginine peptides to SPIO, which greatly enhance SPIO uptake into many cell types. 68,80 The potential of in vivo cell tracking has been demonstrated in several systems including SPIO loaded T cells. 31 Objects as diminutive as single cells were able to be monitored since the T2 relaxation effect of the sequestered magnetic nanoparticles is exerted over a region larger than that of the cell itself.…”
Section: Cell Trackingmentioning
confidence: 99%
“…Recently, nanoparticlebased PET agents have been developed for multimodal imaging, however, only a few combined PET/MRI probes have been reported to date, while the majority of the bimodal probes have been developed for use in optical imaging in combination with either PET or MRI. [1], [20], [21], [22], [23] and [24]. Chen and coworkers reported nanoparticle-based probe for dual-modality PET/MRI, by using MnMEIO as MRI agent and 124 I for PET [25].…”
Section: Introductionmentioning
confidence: 99%
“…It is known to act as a 'vector' to direct the protein into the cell nucleus through the nuclear pore complex, [17,18] and was recently applied to Au-and dextran-coated iron oxide nanoparticles for their targeting to cell nuclei. [19][20][21][22] Different from these previous functionalization steps, our approach is to conjugate biotinylated NLS to monodisperse Fe 3 O 4 nanoparticles through NeutrAvidin (NAv) and a surfactant combination of polyethylene glycol (PEG) and dopamine (DPA), or 4-(2-aminoethyl)benzene-1,2-diol. DPA can form a strong chelate chemical bond with the iron oxide surface, [23,24] and PEG has been used widely to protect nanoparticles for their stabilization under physiological conditions.…”
Section: Introductionmentioning
confidence: 99%